2015
DOI: 10.3389/fmars.2015.00005
|View full text |Cite
|
Sign up to set email alerts
|

Absence of genetic differentiation in the coral Pocillopora verrucosa along environmental gradients of the Saudi Arabian Red Sea

Abstract: The Red Sea is the world's northernmost tropical sea. The 2000 km long, but narrow basin creates distinct environmental conditions along its latitudinal spread. The Red Sea displays a pronounced salinity gradient from 41 to 37 PSU (north to south) with an opposing temperature gradient from 21 to 27 • C in the north to 27-33.8 • C in the south. The Red Sea further displays a decreasing nutrient gradient from south to north that can also influence underwater light fields due to higher phytoplankton content and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 87 publications
2
54
0
Order By: Relevance
“…However, Symbiodi nium identity was not determined in these studies and it remains uncertain as to whether the here-proposed mechanism of symbiont flexibility in P. lutea can be generalized. Overall, coral populations along reefs in the Red Sea seem to be connected (Robitzch et al 2015), but host genotypic divergence may have played a role in the observed host-symbiont pattern in P. lutea as has been shown for Seriatopora hystrix in the Great Barrier Reef (Bongaerts et al 2010). …”
Section: Environmental Patterns and Physiological Plasticity In Relatmentioning
confidence: 80%
“…However, Symbiodi nium identity was not determined in these studies and it remains uncertain as to whether the here-proposed mechanism of symbiont flexibility in P. lutea can be generalized. Overall, coral populations along reefs in the Red Sea seem to be connected (Robitzch et al 2015), but host genotypic divergence may have played a role in the observed host-symbiont pattern in P. lutea as has been shown for Seriatopora hystrix in the Great Barrier Reef (Bongaerts et al 2010). …”
Section: Environmental Patterns and Physiological Plasticity In Relatmentioning
confidence: 80%
“…Although the sample size of our study preclude an exhaustive analyses of inter- and intra-population variation, other studies have also shown small or no regional differentiation for this species along the strong environmental gradients in the Red Sea. Robitzch, et al51 investigated the population structure of P. verrucosa based on 360 samples collected between Al-Wajh (2-WAJ) and Doga (5-DOG) with the same mitochondrial marker as used in this study, and with nine additional microsatellite markers. They did not find any differentiation of the coral populations over a distance of 850 km.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical simulations presented by Zhan et al () indicated that that eddies may considerably impact coastal current variability and cause substantial vertical transport at the coastal boundary due to the interaction with the boundary. The impact of eddies on coral reef communities has been proposed by Robitzch et al (), who infer that eddies may substantially contribute to the dispersal of coral larvae, and by Kürten et al (), who showed that coral reef biota assimilate macronutrients from the oceanic catchment in the Red Sea. As has been observed in the open ocean (Gaube et al, ; McGillicuddy et al, ; Rodríguez et al, ), eddies may appreciably impact primary productivity of the Red Sea.…”
Section: Introductionmentioning
confidence: 97%